Waste not, want not ; Trial in exile ; Chefs on Parade [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Deals with interviews with Mrs. Imelda Marcos about her life aftr Ferdinand's death in New York City ; industrial waste as an issue in environment and health of people in Ormoc, Leyte; and interview with a group of Filipino chefs in salon cullinaire competition in Singapore.